1996
DOI: 10.1038/ki.1996.533
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase induction with renal transplant rejection or infection

Abstract: Nitric oxide (NO) is readily oxidized to nitrate and nitrite and NO activates guanylyl cyclase, increasing cyclic GMP levels. To determine if nitric oxide synthase (NOS) is present in urine collected daily from patients following renal transplantation, we evaluated NOS activity in the leukocyte-rich particulate fraction and measured nitrate, nitrite, and cyclic GMP levels in the supernatant fraction of the urine. Reverse transcriptase-PCR and cDNA sequencing confirmed the presence of inducible NOS (iNOS) in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 29 publications
0
15
2
Order By: Relevance
“…In several disease processes that affect the urinary tract, changes in iNOS activity have been identified. For example, in both urinary infection and renal transplant rejection, iNOS activity is increased [7,8]. In patients with interstitial cystitis, particulate NOS activity in the urine is decreased compared with controls [25].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In several disease processes that affect the urinary tract, changes in iNOS activity have been identified. For example, in both urinary infection and renal transplant rejection, iNOS activity is increased [7,8]. In patients with interstitial cystitis, particulate NOS activity in the urine is decreased compared with controls [25].…”
Section: Discussionmentioning
confidence: 96%
“…iNOS is elevated during disease processes in the urinary tract [7,8]. It has been reported that NO production may be involved in the association between inflammation and human malignancies, including bladder cancer [9].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, conflicting data on NO x levels in both serum and urine have been found in acute renal allograft rejection (15)(16)(17)(18). Using immunohistochemistry, we recently found an increase in interstitial and glomerular iNOS expression and a decrease in glomerular eNOS expression in patients with AR compared with control kidneys (17).…”
mentioning
confidence: 98%
“…Measurements of the stable end-products nitrite and nitrate (NO x ) suggest a role for NO¡ in acute rejection (AR) (15,16). In humans, conflicting data on NO x levels in both serum and urine have been found in acute renal allograft rejection (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…In the urinary bladder, NO formation is increased severalfold in bladder inflammatory conditions such as infectious, interstitial and irradiation cystitis [9,10]. Increase in urinary nitrate indicates systemic formation of NO in connection with diseases, such as infective gastroenteritis, or under conditions such as cardiac and renal allograft rejections [11][12][13]. Urinary nitrite, on the other hand, is the major end product of local NO formation in the urinary tract since there are no known mechanisms for nitrite conversion into nitrate in the urinary tract [14].…”
Section: Introductionmentioning
confidence: 99%